Pengaruh Penggunaan Pati Sukun sebagai Edible Coating terhadap Mutu Fisik dan Kimia Buah Tomat (Solanum lycopersicum L.) Selama Penyimpanan - Findi Citra Kusumasari; Irene Ratri Andia Sasmita; Emi Kurniawati; Mohammad Mardiyanto; Angga Prasetyo (Journal of Food Security and Agroindustry, 2026)
Tomato (Solanum lycopersicum L.) is a climacteric horticultural commodity that is highly susceptible to postharvest quality deterioration due to high respiration and transpiration rates. This study aimed to evaluate the effects of breadfruit (Artocarpus altilis) starch concentration as an edible coating material and storage duration at 25 °C on the physical and chemical quality of tomato fruit. The study used a completely randomized design (CRD) with a combination of breadfruit starch concentrations of 0%, 1%, 2%, 3%, 4%, 5%, and 6%, and storage durations of 0, 2, 4, 6, 8, and 10 days. The observed parameters included vitamin C content, weight loss, total soluble solids, texture, and pH. The results showed that breadfruit starch concentration and storage duration significantly affected vitamin C content, weight loss, and total soluble solids, but had no significant effect on texture and pH. The best treatment was obtained at a breadfruit starch concentration of 6%, which maintained the highest vitamin C content, minimized weight loss, and resulted in a lower final total soluble solids value compared with the other treatments. Breadfruit starch-based edible coating has the potential to be used as an environmentally friendly postharvest technology to maintain quality and extend the shelf life of tomato fruit.